Interface entre saúde e educação o processo de encaminhamento infantojuvenil a um serviço público de fonoaudiologia paulista - Moreira, Luiza Salles [UNIFESP] (2019)
The research aims to outline the profile and analyze the process of infant-juvenile referral to speech-language therapy at Cubatão's Central Ambulatory of Pediatric Specialties. It is a descriptive retrospective study. The approach of this study is qualitative, through documentary research to analyze the demand and the referral flow for speech and hearing care, from January to December 2017. To study this population, data on gender, age, school year, diagnostic hypothesis, referral flow and reason/complaint of the consultation were collected. The instrument used for data collection were the speech-language records of the outpatient clinic. The hypothesis of this research is that the demand is only sent to speech therapy when the communication pathologies are already installed, at an advanced level and late. The research results show that the complaints and diagnostic hypotheses vary according to the age and education level of the juvenile population. Referral reports presented child-centered complaints, exempting family, school and society from the reported difficulties. The synthesis of the sample profile shows the prevalence of males, aged between 6 and 10 years old, who attend elementary school. Phonological alterations were the most prevalent diagnostic hypotheses in the preschool population and, in elementary school, written language alterations and more than one hypothesis. Education was responsible for most referrals. In the reports of kindergarten, a single complaint predominated, being the speech-language disorders present in all referrals, with the main reason being difficulties regarding speech. In primary school, school reports with two or more complaints predominated, and complaints were categorized as speech-language disorders as the main reason for referral (mainly reading and writing, but also complaints regarding the child's behavior in the classroom and poor school performance/learning). From the research data, a technical production was proposed: “Speech-Language Pathology Health Promotion Guide”. The Guide aims to promote the interface between health and education, instruct the teacher to identify, discriminate and scale complaints of speech language disorders in an agile and assertive manner, and provide the therapist with a clearer understanding of the reasons that led the school to the speech pathology referral.